2021
DOI: 10.1002/ajoc.202100497
|View full text |Cite
|
Sign up to set email alerts
|

Iodine(III)‐Promoted Ring Expansion Reactions: A Metal‐Free Approach toward Seven‐Membered Heterocyclic Rings

Abstract: A metal‐free approach for the synthesis of seven‐membered heterocycles (chromane, thiochromane) or rings fused with heterocycles (furan, indole, pyrrole, and thiophene) is described. The salient feature of the strategy is based on the ring expansion of methylenic heterocycles mediated by the iodine(III) reagent HTIB (PhI(OH)OTs) in aqueous acetonitrile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…During our study of heterocyclic ring expansion reactions using hypervalent iodine, we observed that some of the substrates prepared via Wittig olefination were easily isolated. However, some ketones were decomposed during the work-up process or obtained in very low yields upon exposure to the Wittig reaction [ 23 , 24 ]. To investigate the reason, we decided to observe the decomposition behavior of the expected alkenes via a series of heterocyclic substrates.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…During our study of heterocyclic ring expansion reactions using hypervalent iodine, we observed that some of the substrates prepared via Wittig olefination were easily isolated. However, some ketones were decomposed during the work-up process or obtained in very low yields upon exposure to the Wittig reaction [ 23 , 24 ]. To investigate the reason, we decided to observe the decomposition behavior of the expected alkenes via a series of heterocyclic substrates.…”
Section: Resultsmentioning
confidence: 99%
“…After the unsuccessful isolation of the expected olefinic product for 4n, our subsequent goal was to capture the intermediate (olefinic product) before decomposition in the work-up process. Our strategy was to generate the resulting methylene product but using a minimal amount of Wittig reagent (1.2 equiv) with the aim of minimizing any complexation in the subsequent step, where the reaction mixture was directly exposed (without work-up and isolation process) to an iodine(III) reagent (Hydroxy(tosyloxy)iodobenzene (HTIB) dissolved in CH3CN:H2O (9:1 v/v)), with the potential to induce rearrangement and incorporate the exo-methylenic carbon into the ring (Scheme 5) [23]. After the study of protected (EWG) indole derivatives, we extended our investigation to pyridine derivatives (such as isoquinolinones) to determine the stability of the resulting methylene products.…”
Section: Heterocyclic Wittig Olefinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Khan et al reacted ketone 78 with potassium tert -butoxide, Ph 3 PCH 3 Br and diethyl ether, which resulted in the synthesis of chromane intermediate 79 . The synthesized chromane was then treated with HTIB catalyst in the presence of acetonitrile and water as solvent to synthesize seven-membered heterocycle 80 in a good yield ( Scheme 24 ) [ 54 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…[18][19][20] HTIB has garnered significant interest among researchers because of its economic viability and commercial availability. [21][22][23] The conversion process from 1,2-dihydronaphthalene (1) derivatives into the corresponding indane derivatives using HTIB is highly efficient and straightforward. 2 In our previous work, we utilized 1,2-dihydronaphthalene derivatives as substrates with HTIB to achieve ring-contracted products (indanes) with different functionalities.…”
mentioning
confidence: 99%